The effects of subjective life expectancy on volunteerism in older adults. (July 2019) - Lee, Kyuho; Kim, Dahee; Gilligan, Megan; Martin, Peter
Previous studies used chronological age to examine the relationship between aging and volunteerism. In the current study, we examined the influence of subjective life expectancy (SLE) on volunteering based on the socioemotional selectivity theory emphasizing that older adults focus on very close relationships. Data of 11, 203 older adults, 55 to 74 years old ( M = 65.0, SD = 5.6), from five waves (2006–2014) of the Health and Retirement Study were included. Growth curve modeling results showed that older adults with higher SLE scores at baseline not only spent more time volunteering but also showed a slower decrease in volunteering over time. Furthermore, changes in older adults' SLE were associated with a change in volunteering. The findings may show the relative importance of close relationships and social activities for older adults and contribute to demystifying the differences shown in the volunteer participation among older adults.